2004
DOI: 10.1007/s00497-004-0223-y
|View full text |Cite
|
Sign up to set email alerts
|

AVAG2 is a putative D-class gene from an ornamental asparagus

Abstract: Members of the AGAMOUS (AG) family of MADS-box genes play important roles in regulating the development of reproductive organs in flowering plants.To elucidate the molecular mechanisms of floral development in Asparagus virgatus, we isolated and characterized an Asparagus AG-homologue, AVAG2. AVAG2 contains an open reading frame that encodes a deduced protein with 234 amino acid residues. Phylogenetic analysis indicated that AVAG2 belongs to the D-lineage of the AG gene family. AVAG2 mRNA was detected in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…b bract, im inflorescence meristem, fm floral meristem, fp floral primordium, otp outer tepal primordium, lp lip primordium, lpj lip projection, ot outer tepal, it inner tepal, l lip, c column, p pollinium, r rostellium, o ovule, ow ovary wall, s stigma, sc stigmatic cavity, aoa apex of anther, v viscidium, t tegula. Bar: 0.5 mm (Vandenbussche et al 2003;Kramer et al 2004;Yun et al 2004b). In particular, Kramer et al (2004) found that AGlike genes have diagnostic amino acid motifs in the Cterminal regions that are denoted as AG motifs I and II.…”
Section: Cdna Cloning Of Ag-like Genes From Phalaenopsismentioning
confidence: 99%
See 1 more Smart Citation
“…b bract, im inflorescence meristem, fm floral meristem, fp floral primordium, otp outer tepal primordium, lp lip primordium, lpj lip projection, ot outer tepal, it inner tepal, l lip, c column, p pollinium, r rostellium, o ovule, ow ovary wall, s stigma, sc stigmatic cavity, aoa apex of anther, v viscidium, t tegula. Bar: 0.5 mm (Vandenbussche et al 2003;Kramer et al 2004;Yun et al 2004b). In particular, Kramer et al (2004) found that AGlike genes have diagnostic amino acid motifs in the Cterminal regions that are denoted as AG motifs I and II.…”
Section: Cdna Cloning Of Ag-like Genes From Phalaenopsismentioning
confidence: 99%
“…These motifs appear to be conserved in many AG homologs in angiosperms (Kramer et al 2004), although their functions have not yet been characterized. In addition, upon alignment of the known D-class genes, Yun et al (2004b) found a nine amino acid motif downstream of the AG motif II in monocots which is called MD motif. When we aligned the known AG-like genes with PhalAG1 and PhalAG2, we found that both bear the AG motifs I and II at their C-termini (Fig.…”
Section: Cdna Cloning Of Ag-like Genes From Phalaenopsismentioning
confidence: 99%
“…D-lineage AG-like genes were isolated from A. virgatus (AVAG2) and Agapanthus praecox (ApMADS2). AVAG2 was expressed in stamens and carpels during the early stage of floral development, and expressed in ovules at later stages of floral development (Yun et al, 2004b). ApMADS2 has not been characterized yet.…”
Section: -2) Lily-type Flowers-a Perianth With Two Petaloid Whorlsmentioning
confidence: 99%
“…In monocots, a similar expression profile has been reported for the rice gene MADS13, its maize ortholog ZAG2, the lily (Lilium longiflorum) gene LMADS2, and MADS1 from hyacinth (Hyacinthus orientalis). However, expression in stamens has also been shown for monocot AGL11 lineage genes, for example, MADS21 in rice (Dreni et al, 2007) and AVAG2 in asparagus (Asparagus officinalis; Yun et al, 2004). Thus, it seems plausible that the angiosperm AGL11 lineage ancestral gene had an expression pattern already restricted to the ovules and annexed ovary tissues and that the conservation of this expression domain, and the related D-function, is less strict in monocots when compared with core eudicots.…”
Section: Conservation Of Expression Of Ag and Agl11 Lineage Genesmentioning
confidence: 99%